2018
DOI: 10.1007/s00227-018-3419-7
|View full text |Cite
|
Sign up to set email alerts
|

How do food sources drive meiofauna community structure in soft-bottom coastal food webs?

Abstract: Meiofauna have a strong role in the functioning of coastal ecosystems but how their food sources affect their community structure remains unclear, likely due to the influence of abiotic parameters and the small size of these organisms. The meiofauna and their potential food sources were sampled in several intertidal habitats (i.e. mudflat, seagrass bed, sandflat) of the Marennes-Oléron Bay, France, and the Sylt-Rømø Bight, Germany, to assess the relationships between habitat characteristics and meiofauna commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 96 publications
(129 reference statements)
0
14
0
Order By: Relevance
“…SOM compositions differed between habitats, with a much higher influence of diatoms in the SOM from the sandflat of the Sylt-Rømø Bight (van der Heijden et al, 2018), as demonstrated by its higher δ 13 C values and higher proportions of diatom FA markers. Isotope compositions of SOM also varied between sediment layers with SOM being more depleted in 13 C in the sub-surface layers, as already observed in the Schelde estuary (Moens et al, 2014).…”
Section: Distinction Of Spom Som and Primary Producers Based On Bulkmentioning
confidence: 98%
See 4 more Smart Citations
“…SOM compositions differed between habitats, with a much higher influence of diatoms in the SOM from the sandflat of the Sylt-Rømø Bight (van der Heijden et al, 2018), as demonstrated by its higher δ 13 C values and higher proportions of diatom FA markers. Isotope compositions of SOM also varied between sediment layers with SOM being more depleted in 13 C in the sub-surface layers, as already observed in the Schelde estuary (Moens et al, 2014).…”
Section: Distinction Of Spom Som and Primary Producers Based On Bulkmentioning
confidence: 98%
“…The intermediate δ 13 C values of SOM limited determining the contributions of the different primary producers in SOM composition, clearly highlighting the importance of the combination of SI and FA markers. Based on FA analyses, SOM was mostly made up of diatoms and bacteria, with very low contributions of seagrass or terrestrial material, even in seagrass beds where the load of seagrass material in the sediment was high (Lebreton et al, 2011;van der Heijden et al, 2018). Diatoms from the SOM mainly originated from the microphytobenthos, as highlighted by the high δ 13 C values of the diatom marker 20:5(n-3) (i.e.…”
Section: Distinction Of Spom Som and Primary Producers Based On Bulkmentioning
confidence: 99%
See 3 more Smart Citations